Implementación de un sistema de contabilidad de costos por procesos en la empresa de plásticos Cotopaxi s.a. ubicada en la parroquia Chantilín, del cantón Saquisilí de la provincia de Cotopaxi, al período del 01 de agosto al 31 de diciembre del 2013 - Almache Jacho, Hugo Ramiro (2016)
The present research work is the implementing a costs accounting system for processes in the Plastics Enterprise Cotopaxi S.A., located in the Chantilín parish, Saquisilí Canton from Cotopaxi Province. The used methodology in the field investigation and the inductive the author Mary Moreno method applied based on the facts observation for reaching to conclusions by applying a variety of techniques and data collection instruments such as direct observation, interviews and documentary sources review of costing processes, This accounting proposal contemplates the development of application forms, standards and adequate procedures which allow collecting, record and report data on production cost and provide information to the Department to provide the adequate decisions ensuring value for money, This accounting proposal envisages the development of forms, rules and procedures that allow ford collecting, recording and reporting production cost data and providing information to the Direction that facilitate the proper decision making by ensuring the resource optimization and thus, lower production of costs and this way get greater profitability for the enterprise. The sufficiency which can develop this research will depend on the implementation that the enterprise can give to the same.